Avaliação dos efeitos da terapia fotodinâmica com hipericina-glucamina no tratamento da doen ça periodontal induzida em ratos - Macedo, Paula Delello [UNESP] (2014)
The Photodynamic Therapy (TFD) has shown satisfactory results when coupled with mechanical treatment of periodontal diseases. The aim of this work was to evaluate whether PDT with the photosensitizer hypericin-glucamine, enabled by amber LED (34.10 J/cm2) and combined with scaling and root planning (RAR), promotes better repair of the periodontal disease induced experimentally in rats. The periodontal diseases was installed by randomly inserting ligatures in the grooves of the superior second molars. The bandages were removed after 15 days and the animals were randomized into 4 experimental groups (n = 5): IPD group (Induced Periodontal Disease); RAR group; TFD group; and RAR+TDF group. The animals were sacrificed after 7, 15 and 30 days of the performed treatment. Digital microtomography and histometric analyses were carried out on their hemimaxillas. Shapiro-Wilk normality test was applied to data. The groups were assessed among each other and parametric data were evaluated using ANOVA test. All tests were conducted with p<0.05. Statistical differences were not observed among the groups. Therefore, we concluded that TFD combined with RAR or isolated obtained similar results to scaling and root planning.